The incidence of unpleasant dreams after sub-anaesthetic ketamine - Mark Blagrove (Psychopharmacology, 2009)
Ketamine is an N-methyl-D-aspartate (NMDA)receptor antagonist with psychotogenic effects and for whichthere are diverse reports of whether pleasant or unpleasantdreams result during anaesthesia, post-operatively or aftersub-anaesthetic use. The aim was to assess in healthy volunteers the incidence ofunpleasant dreams over the three nights after receiving asub-anaesthetic dose of ketamine, in comparison to placebo,and with retrospective home nightmare frequency as acovariate.Thirty healthy volunteers completed questionnairesabout retrospective home dream recall and were then giveneither ketamine or placebo. Ketamine resulted in significantly more meandream unpleasantness relative to placebo and caused athreefold increase in the odds ratio for the incidence of anunpleasant dream. The number of dreams reported over thethree nights did not differ between the groups. Theincidence of unpleasant dreams after ketamine use waspredicted by retrospectively assessed nightmare frequencyat home.Ketamine causes unpleasant dreams over thethree post-administration nights. This may be evidence of aresidual psychotogenic effect that is not found on standardself-report symptomatology measures or a result of disturbedsleep electrophysiology. The results have theoretical implications for the relationship between nightmares and schizotypy.